2009
DOI: 10.1128/ec.00007-09
|View full text |Cite
|
Sign up to set email alerts
|

Yap1-Regulated Glutathione Redox System Curtails Accumulation of Formaldehyde and Reactive Oxygen Species in Methanol Metabolism of Pichia pastoris

Abstract: The glutathione redox system, including the glutathione biosynthesis and glutathione regeneration reaction, has been found to play a critical role in the yeast Pichia pastoris during growth on methanol, and this regulation was at least partly executed by the transcription factor PpYap1. During adaptation to methanol medium, PpYap1 transiently localized to the nucleus and activated the expression of the glutathione redox system and upregulated glutathione reductase 1 (Glr1). Glr1 activates the regeneration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 55 publications
(54 reference statements)
1
43
0
Order By: Relevance
“…PpYAP1 can act as a regulator of the redox system in Pichia pastoris. It plays an important role in the defense against oxidative stress by activating the expression of other antioxidative genes involved in the glutathione-based antioxidant system (55,56). Based on our results and previous research, we propose the following hypothesis to address the issue of how laccase expression is linked to defense mechanisms like enhanced glutathione production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PpYAP1 can act as a regulator of the redox system in Pichia pastoris. It plays an important role in the defense against oxidative stress by activating the expression of other antioxidative genes involved in the glutathione-based antioxidant system (55,56). Based on our results and previous research, we propose the following hypothesis to address the issue of how laccase expression is linked to defense mechanisms like enhanced glutathione production.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has revealed that ScYAP1 is an important transcription factor in Saccharomyces cerevisiae, in which it can stimulate the expression of several genes of the glutathionedependent antioxidative system, such as GLR1, GPX2, and GSH1 (28, 38-40, 53, 55). Recent studies have shown that the PpYAP1-regulated glutathione redox system plays an important role in the detoxification of reactive oxygen species in the methanol metabolism of Pichia pastoris (55). PpYAP1 can act as a regulator of the redox system in Pichia pastoris.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a transcription factor termed Yap1p plays an important role in the upregulation of GSH-related enzymes in P. pastoris. 15,16) In that the PpYap1p-depleted strain proved sensitive to H 2 O 2 but not to HCHO, methylotrophic yeasts must have an alternative transcriptional regulatory system to controll the expression of the genes for HCHO resistance.To date, in the budding yeast Saccharomyces cerevisiae, stress-inducible transcription factors Msn2p/ Msn4p and heat shock protein Ssa4p, and their carrier Msn5p, have been reported to play important roles in protecting cells from stress-induced cell death. [17][18][19][20][21] Among these factors, we focused on Msn5p, which belongs to the importin-family and participates in the nuclear export of several proteins.…”
mentioning
confidence: 99%
“…Recently, the mechanisms by which methylotrophic yeasts respond to oxidative stress derived from H 2 O 2 or other reactive oxygen species (ROS) were elucidated in P. pastoris. 18,19) This knowledge should improve the utility of the P. methanolica gene expression system, as it is necessary to understand not only the scavenging system for ROS but also the mechanism of response to ROS.…”
mentioning
confidence: 99%